Development of proposals on passenger questionnaires for regular urban passenger transport - S. A. Azemsha; V. M. Morozov (Вестник СибАДИ, 2022)
Introduction. Public transport in the life of modern cities plays a significant role in the formation of urban transport systems, thereby affecting the environment, the quality of people’s life, their health, road safety, etc.Knowledge of the existing features of public transport functioning will allow for competent intervention in the operation of this system, increase its attractiveness and attract additional passengers. It is possible to obtain such knowledge by polling system users – passengers. Transport surveys around the world are widely used to develop measures to improve the operation of transport, as well as to evaluate their effectiveness.This article provides an analysis of the regulatory documents governing the conduct of transport surveys, as well as scientific literature, including foreign ones, describing both the conduct and results of such surveys. The relevance of the topic is due to the need to generalize the experience of conducting transport surveys and the implementation of the obtained quintessence when questioning passengers in the Republic of Belarus. Tasks to be solved:– analysis of the legislation of the Republic of Belarus on the subject of the study;– analysis of the experience of conducting transport surveys abroad;– development of general recommendations for the structure, content and method of carrying out a transport survey;– development and placement of a questionnaire for users to fill out.The purpose of the work is to develop the structure, content and method of conducting a transport survey of passengers in the cities of the Republic of Belarus, taking into account the current legislation of the country and the experience of implementing such events in foreign countries.Scientific novelty lies in the use of scientific methods of analysis and synthesis in the development of the structure and content of the transport survey.Materials and methods. When writing the article, analysis and synthesis scientific methods were used.Results. Based on the results of the article, the structure of the transport survey and methods for conducting it for the conditions of the Republic of Belarus were developed.Discussion and Conclusions. The obtained structure of the transport survey and the method of its conduct correspond to the conditions for the functioning of the urban passenger transport of the Republic of Belarus and allow obtaining initial information to substantiate the ways of further development of this type of transport.